The CORRELATION BETWEEN MORPHOLOGICAL AWARENESS AND VOCABULARY MASTERY OF FOURTH-SEMESTER STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM AT ARTHA WACANA CHRISTIAN UNIVERSITY - Poilema, Evandertus; Hambandima, Erni Selfina Nggala; Nenotek, Seprianus Arwadi (Journal of Language, Education, Literature, and Culture, 2024)
The correlation between morphological awareness and vocabulary mastery is a crucial area of investigation within language education. Understanding this relationship is important because it can inform effective teaching strategies that enhance vocabulary acquisition among students. Research shows a general link between morphological awareness and vocabulary mastery but lacks focus on specific educational stages. This study addresses that gap by examining fourth-semester students in the English Education Study Program at Artha Wacana Christian University, who have just completed their morphology course, to see how well they apply this knowledge to improve their vocabulary. Thus, the researcher formulate the research problem as follow: Is there any correlation between morphological awareness and vocabulary mastery of fourth-semester students of the English Education Study Program at Artha Wacana Christian University? The research utilized a quantitative approach with a correlation study design. Morphological awareness tests and vocabulary level tests were administered to a sample of 20 fourth-semester students. The findings revealed a correlation coefficient (rxy) of 0.802, which exceeds the 5% and 1% levels of significance, indicating a very high correlation between the two variables. These results suggest that enhancing morphological awareness could be an effective strategy for improving vocabulary mastery. Therefore, educators should consider incorporating morphological awareness activities into their teaching practices to support vocabulary development in their students